Developing a simulation-based learning model for acute medical education during COVID-19 pandemic with Simulation via Instant Messaging – Birmingham Advance (SIMBA). Issue 2 (8th April 2022) - Wallett, Lucy; Chen, Wentin; Thomas, Lucretia; Blaggan, Parisha; Ooi, Emma; Zhou, Dengyi; Hanania, Thia; Ng, Cai Ying; Evans, Nia; Morgan, Georgia; Allison, Issy; Pan, Carina Synn Cuen; et al.
Abstract : Simulation-based learning (SBL) is well-established in medical education and has gained popularity, particularly during the COVID-19 pandemic when in-person teaching is infeasible. SBL replicates real-life scenarios and provides a fully immersive yet safe learning environment to develop clinical competency. Simulation via Instant Messaging – Birmingham Advance (SIMBA) is an exemplar of SBL, which we previously showed to be effective in endocrinology and diabetes. Previous studies reported the efficacy of SBL in acute medicine. We studied SIMBA as a learning intervention for healthcare professionals interested in acute medicine and defined our aims using the Kirkpatrick model: (i) develop an SBL tool to improve case management; (ii) evaluate experiences and confidence before and after; and (iii) compare efficacy across training levels. Three sessions were conducted, each representing a PDSA cycle (Plan-Do-Study-Act), consisting of four cases and advertised to healthcare professionals at our hospital and social media. Moderators facilitated progression through 25 min simulations and adopted patient and clinical roles as appropriate. Consultants chaired discussion sessions using relevant guidelines. Presimulation and postsimulation questionnaires evaluated self-reported confidence, feedback and intended changes to clinical practice. Improvements were observed in self-reported confidence managing simulated cases across all sessions. Of participants, 93.3% found SIMBA applicable to clinical practice, while 89.3% and 88.0% felt SIMBA aided personal and professional development, respectively. Interestingly, 68.0% preferred SIMBA to traditional teaching methods. Following participant feedback, more challenging cases were included, and we extended the time for simulation and discussion. The transcripts were amended to facilitate more participant-moderator interaction representing clinical practice. In addition, we refined participant recruitment over the three sessions. In cycle 1, we advertised incentives: participation counted towards teaching requirements, certificates and feedback. To rectify the reduction in participants in cycle 2, we implemented new advertisement methods in cycle 3, including on-site posters, reminder emails and recruitment of the defence deanery cohort.